The divine guidance of the Qur'an on poverty alleviation - Tahir, Ibrahim Nuhu (2015)
The world is suffering from chronic poverty, with around 3 billion of its population living below $2.50 per day and 80% living below $10 . The effects of poverty indiscriminately cut across race, nationality and religion. Multiple stakeholders in the public and private sectors have tried numerous methods to alleviate poverty. Different approaches have been used to at least remove hardcore and extreme poverty if not eradicate poverty completely. Unfortunately, regardless of the financial and human resources that have been dedicated to this effort there has been a failure except in a few instances. One of the causes of that failure is the abandonment of the methodology of the early generations, such as Umar ibn Abd Al-Aziz (rahimahullah), who fully depended on the Qur’an and Sunnah in his administration. Development has been taken as a completely secular activity without any connection to the religion of Islam. This secular approach to economics is why calamities have befallen the Ummah and the world in general as it is an abandonment of the infallible guidance of the Qur’an and Sunnah. This paper presents two approaches: The Islamic Spiritual and Physical approaches to poverty alleviation. It explains the injunctions Qur’an has provided: Iman, Taqwa, Zakat, Sadaqah, etc on how to meet the needs of the underprivileged. The paper uses the example of Umar to illustrate the benefit of following the Qur’an and Sunnah of the Prophet (e) using the understanding of the companions. His case is a real example of the application of principles laid down by the Qur’an as a guide to poverty alleviation through the Maqasid al-Shari'ah.